A study of hemodynamic medicine use in intensive cardiac care unit of dr. Soedarso regional public hospital, Pontianak - Shoma Rizkifani; Intan Khairunnisa; Eka Kartika Untari (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Hemodynamic medicines are important to recover patients with a critical period in the ICCU. Hemodynamic medicines have a small range of dose so that it has a large effect on the therapy. Therefore, a study on the use of hemodynamic medicines and doses is necessarily conducted. This study aims to investigate the use and doses of hemodynamic medicines administered to patients in the ICCU of dr. Soedarso Hospital Pontianak. This study is observational research with a descriptive cross-sectional design. The research sample was 49 patients who had met the inclusion criteria. The data were analyzed descriptively to describe the frequency and percentage. The results show that a single hemodynamic medicine is administered to 65% of the patients and a combination of hemodynamic medicines is administered to 35% of the patients. The single medicine refers to dobutamine administered to 84.4% of the patients. Meanwhile, the combination of hemodynamic medicines consists of dobutamine and norepinephrine that are administered to 52.9% of the patients. The doses of hemodynamic medicines frequently administered to patients are 3-5 Î¼g/kg/min dobutamine, 3-10 Î¼g/kg/min dopamine, 0.01-2-2 Î¼g/kg/min norepinephrine, and 1 mg/ml epinephrine. This study concludes that dobutamine (inotropic) is the most frequently used single hemodynamic medicine, and norepinephrine (vasopressor) is the most frequently used combined hemodynamic medicine for the ICCU patients at dr. Soedarso Regional Public Hospital, Pontianak.